2019
DOI: 10.1021/acs.jpcc.9b07380
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Oligomerization at the Air–Water Interface Modified by Competitive Adsorption of Surfactants

Abstract: Amphiphilic organic compounds that accumulate naturally on the outermost layers of aqueous aerosols totally change the mechanisms involved in the uptake and reactions of volatile organic compounds adsorbed on the surfaces. By means of mass spectrometry of aqueous microjets, we examined how quaternary alkylammonium cations Me(CH 2 ) n−1 N + Me 3 (n = 1, 4, 8, 10, 12, and 14) and nonionic octan-1-ol influence acid-catalyzed oligomerization of gaseous isoprene (ISO) at the air−water interface. The oligomerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Significantly, the gas-phase basicities of ISO and TMA are widely different, but their titration curves are identical within experimental error. Similar titration curves were obtained with other gas-phase olefins and terpenes. We infer that the common equivalence point at pH 1/2 ∼ 3.6 is a property of OTL water rather than of the gases being protonated.…”
Section: Isoprene Experimentssupporting
confidence: 75%
See 1 more Smart Citation
“…Significantly, the gas-phase basicities of ISO and TMA are widely different, but their titration curves are identical within experimental error. Similar titration curves were obtained with other gas-phase olefins and terpenes. We infer that the common equivalence point at pH 1/2 ∼ 3.6 is a property of OTL water rather than of the gases being protonated.…”
Section: Isoprene Experimentssupporting
confidence: 75%
“…This was confirmed by the isotope effects, sometimes very large, observed in the protonation/deuteration of several gases on H 2 O/D 2 O microdroplets, ,, and by the sensitive dependence of the extent of protonation (and polymerization) of olefins on molecular structure. The relative rates of chain propagation, chain transfer, and hydride abstraction reactions of the carbocations resulting from the protonation of olefins proved to be quite sensitive to inductive and conjugative effects. , …”
Section: Isoprene Experimentsmentioning
confidence: 99%
“…In previous studies, , we found that the uptake of gaseous unsaturated hydrocarbons and subsequent chain reactions on the surface of water are governed by chemistry that differs from that in the bulk solution. For example, whereas conjugated CC bonds suppress the CP reaction in bulk organic solution, at the air–water interface the CP reaction is promoted. ,, In the present study, partial hydration by interfacial water molecules is found to be a key controlling factor that makes the interfacial reaction unique.…”
mentioning
confidence: 53%
“…For example, whereas conjugated CC bonds suppress the CP reaction in bulk organic solution, at the air−water interface the CP reaction is promoted. 19,35,48 In the present study, partial hydration by interfacial water molecules is found to be a key controlling factor that makes the interfacial reaction unique.…”
Section: R(g) H O (Int) Rh (Int) H O(int)mentioning
confidence: 65%
“…8 The small size of developing aerosol droplets makes it incredibly challenging to directly measure the surface tension, as well as the composition of individual micrometer sized droplets. [17][18][19] Current techniques rely on indirect measurements such as determining the composition of an accumulated aerosol droplet sample.…”
Section: Köhler Theorymentioning
confidence: 99%